Medieval art, architecture and archaeology in London
1 online resource (178 pages).
Keywords: First published in 1991, this book contains papers on various topics including the contribution of archaeology for understanding re-Norman London; medieval and Tudor domestic buildings in the city of London; shops and shopping in medieval London; and the Romanesque architecture of Old St Paul's Cathedral.